Mechanism of Action of Strychni Semen for Treating Rheumatoid Arthritis and Methods for Attenuating the Toxicity - Li, Yuling; Liu, Yifan; Shao, Yumeng; Zhang, Fengcong; Liu, Weidong; Liang, Xiaodong; Chen, Li (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease, which affects the joints and causes significant pain, impairing patient's quality of life. Strychni semen showed promising results to treat RA. However, there are increasing safety concerns in using strychni semen due to its severe toxicity. Aim and Objective: The purpose of this review is to provide insight into using Strychni semen as an alternative medicine to treat RA, as well as to offer a method for the safe application of Strychni semen through processing and compatibility studies. Methods: Publications were retrieved and surveyed from CNKI and PubMed relevant to Strychni semen for a literature review. Results: This article summarized the mechanism of function of strychni semen in treating RA with its anti-inflammatory, analgesic, and immunomodulatory effect. Commonly used methods to attenuate the toxicity of Strychni semen were also discussed in this article. Conclusion: Strychni semen has a good therapeutic effect on RA, mainly by the modulation of immunity with anti-inflammatory and analgesic effects. Also, the reported toxicity of strychni semen can be effectively reduced by processing and compatibility methods. Hence, as an alternative medicine for RA treatment, strychni semen has a broad prospect.
Keywords: Strychnos nux-vomica